Life stressors, hypertensive disorders of pregnancy, and gestational diabetes by race/ethnicity - Forgive Avorgbedor; Thomas P. McCoy; Amita Mittal; Lori Hubbard; Stephanie Pickett (PLoS ONE, 2025)
Background In the United States, adverse pregnancy outcomes, including hypertension before pregnancy (HTN), pregnancy-induced hypertension (PIH) [gestational hypertension and preeclampsia] and gestational diabetes mellitus (GDM) continue to increase. Stressful life events (SLEs) such as serious illness, divorce, are known to impact adverse birth outcomes, e.g., preterm birth, especially among Black women, low-income women, and other minority women than White women. However, there is limited evidence on SLEs adverse pregnancy outcomes. Therefore, the objective of this study is to provide an overview of trends in stressful life events from 2009 to 2020 and their impacts on hypertension before pregnancy, pregnancy-induced hypertension, and gestational diabetes mellitus in the United States and to understand these effects by race/ethnicity. Methods A secondary analysis of Centers for Disease Control and Prevention national Pregnancy Risk Assessment Monitoring System data from 2009 to 2020 was performed. SLEs, HTN before pregnancy, PIH, and GDM, were examined with data visualizations and multivariable weighted log-binomial modeling. Results Any SLE prevalence was 66% to 72%, with Black women having higher SLEs than White women. SLE was associated with HTN before pregnancy (ARR = 1.082), PIH (ARR = 1.059), and GDM (ARR = 1.030). Effects of race/ethnicity differed across these outcomes. Conclusion Greater SLE is associated with adverse pregnancy outcomes. Black women continue to experience higher SLEs and are at higher risk of HTN before pregnancy and PIH. The findings of this study indicate there is an interplay between SLEs, HTN before pregnancy, PIH, and GDM, as well as race/ethnicity. This information is vital for public health efforts to reduce the disparities in adverse pregnancy outcomes.